Comparison the Anti-atherogenic and hypolipidaemic effect of Cod liver oil, pomegranate seed oil and Rosuvastatin in hyperecholestrolemic rats - Humaish, Haider H.; Muslem, Zahraa Z.; Numaan, Karar T. (Journal of Kerbala for Agricultural Sciences, 2019)
Rosuvastatin known is the more "statin moderating the lipid profile by reduction the low density-lipoprotein than the other statin such as atorvastatin, simvastatin and parvostatin". The present study was designed to investigate the anti-atherogenic and the hypolipidemic effect of cod liver oil, pomegranate seed oil and rosuvastatin in hypercholesterolemic rats. Thirty five albino wister rats were divided randomly into five equal groups, the first group served as negative control, all rats were administrated normal saline. The second group as positive control were rats administrated high cholesterol diet for six weeks. The animals in the third, fourth and fifth groups were administrated for 6 weeks as fallow: cod liver oil ( 0.5 mg/kg rat per day), pomegranate seed oil (200 mg/kg/day) and rosuvastatin (0.5 mg/kg/day, orally), respectively; In addition high cholesterol diet. The result revealed the high cholesterol diet in the positive control group caused a significant (p≤0.05) alteration in the lipid profile by increasing the serum total cholesterol (TC), Low density lipoprotein(LDL-c), very low density lipoprotein (VLDL-c) and triglyceride (TGs) as well as significant (p≤0.05) decrease the High-density lipoprotein. Also, the result showed a significant (p≤0.05) increase atherogenic indices by increase the coronary risk index (TC/HDL-C), atherogenic Coefficient (TC-HDL-C/HDL-C) and Atherogenic index of serum Log(TG/HDL-C) compare with negative control group. Indicated results significant (p>0.05) decrease in the level of serum glutathione (GSH) and significant (p≤0.05) increase in the level of malondialdehyde (MDA). While the animals in the group 3,4 and 5 were administrated CLO, PSO and statin the result clarified a significant (p≤0.05) improvement in studied parameters , through decrease the TC, LDL-C, VLDL-C, TG, MDA and atherogenic indices" , and increase the HDL-C and GSH compared with negative and positive control groups.